2020
DOI: 10.1161/strokeaha.119.026205
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Prediction of Dynamic Precision Grip Force Control After Stroke

Abstract: Background and Purpose— Dexterous object manipulation, requiring generation and control of finger forces, is often impaired after stroke. This study aimed to describe recovery of precision grip force control after stroke and to determine clinical and imaging predictors of 6-month performance. Methods— Eighty first-ever stroke patients with varying degrees of upper limb weakness were evaluated at 3 weeks, 3 months, and 6 months after stroke. Twenty-three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…This pattern was also apparent in severely impaired patients. Neither recovery ratio nor severity of impairment co-varied with lesion volume, coherent with recent reports on hand motor recovery (60).…”
Section: Similar Speech-language and Motor Recovery Post-strokesupporting
confidence: 88%
“…This pattern was also apparent in severely impaired patients. Neither recovery ratio nor severity of impairment co-varied with lesion volume, coherent with recent reports on hand motor recovery (60).…”
Section: Similar Speech-language and Motor Recovery Post-strokesupporting
confidence: 88%
“…The ROC analysis further showed that a lesion load > 5.5 cc was highly predictive of both poor bimanual and unimanual recovery (figure 4). Feng, Wang, Chhatbar, Doughty, Landsittel, Lioutas, Kautz and Schlaug 36 also reported that a wCST-LL >5.5 cc in the acute phase, was a strong predictor of unimanual motor recovery (FMA-UE outcome score >25) at three months and Pennati, Plantin, Carment, Roca, Baron, Pavlova, Borg and Lindberg 7 found that wCST-LL >6cc indicated absence of recovery of dynamic precision grip. The present findings show that a similar wCST-LL threshold (>5.5 cc) is also a strong predictor of bimanual hand recovery.…”
Section: Neuroimaging Predictorsmentioning
confidence: 96%
“…In addition, the degree of corticospinal tract damage according to brain imaging and transcranial magnetic stimulation has predictive value for recovery of movement function in the upper extremity after stroke [45,164,165] but corresponding studies have not yet consistently shown its importance for recovery of lower extremity movement function, gait outcomes and for predicting recovery of independent walking [50,[166][167][168]. In future studies, including data on brain structure and function together with a larger sample size may enable subgroup analysis and provide insight in who will benefit the most from EAGT and conventional gait training respectively.…”
Section: Prediction Of Independence In Walkingmentioning
confidence: 99%